1995
DOI: 10.1074/jbc.270.25.15137
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Low Threshold Calcium Channels by Angiotensin II in Adrenal Glomerulosa Cells through Activation of Protein Kinase C

Abstract: In adrenal glomerulosa cells, low threshold voltage-activated (T-type) calcium channels play a crucial role in coupling physiological variations of extracellular potassium to aldosterone biosynthesis. Angiotensin II markedly reduced the activity of these channels by shifting their activation curve toward positive voltage values. This inhibition of the channels resulted in a marked decrease of the cytosolic free calcium concentration maintained by potassium. This effect was abolished by losartan, a specific ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
2
1

Year Published

1998
1998
2022
2022

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 19 publications
0
31
2
1
Order By: Relevance
“…In fact, they have shown that AngII shifts the activation curve of T channels to more negative voltage values, increasing the size of the permissive window of voltage of the channel and therefore allowing more Ca 2ϩ to enter the cell in a steady state manner. In contrast, in our laboratory, we found that AngII shifts the activation curve of T channels to more positive voltages, thus reducing the steady-state current through these channels (10). In this study, Rossier et al (10) demonstrated that AngII exerts a negative modulation on T channels and that this modulation is mediated by protein kinase C (PKC).…”
contrasting
confidence: 46%
See 1 more Smart Citation
“…In fact, they have shown that AngII shifts the activation curve of T channels to more negative voltage values, increasing the size of the permissive window of voltage of the channel and therefore allowing more Ca 2ϩ to enter the cell in a steady state manner. In contrast, in our laboratory, we found that AngII shifts the activation curve of T channels to more positive voltages, thus reducing the steady-state current through these channels (10). In this study, Rossier et al (10) demonstrated that AngII exerts a negative modulation on T channels and that this modulation is mediated by protein kinase C (PKC).…”
contrasting
confidence: 46%
“…The inhibition of the current exerted by the hormone was observed at any voltage, and AngII did not change the shape of the current-voltage curve; threshold, peak, and reversal potentials of the Ba 2ϩ current were not affected by AngII (n ϭ 6). 10). Similarly, losartan prevented AngII action on L-type channels.…”
Section: Inhibition Of L-type Currents Bymentioning
confidence: 99%
“…We thus demonstrate that this ␣ 1H calcium channel is involved in calcium homeostasis and that cytosolic calcium concentrations are modified during neuroendocrine differentiation, due to the overexpression of ␣ 1H calcium channels, induced by permeant analogs of cAMP or IBMX. Such window currents occurring through T-type calcium channels have been reported in other cells (26,29,38). This slight increase in cytosolic calcium concentration may serve in facilitating neurite growth, as proposed in nerve cells (15).…”
Section: Discussionmentioning
confidence: 94%
“…T-type calcium channels generate transient inward currents which rapidly inactivate (exponential time constant 20 ms in our experiments). It was previously shown in other cell models that there may be a range of membrane potentials at which T-type calcium channels are activated, even partially, and at which inactivation is not complete (26). There should thus exist a window of potential allowing a sustained calcium current.…”
Section: The ␣ 1h T-type Calcium Channel Is Involved In a Window Calcmentioning
confidence: 99%
“…The final step in this signal transduction pathway appears to be phosphorylation of the T-type channel by calmodulin-dependent protein kinase II (CaMKII; see below) (27,252). However, not all studies have found an ANG II stimulation of adrenal glomerulosa currents, with reports of either no effect (250) or frank inhibition (103,344).…”
Section: B Hormonal Stimulationmentioning
confidence: 99%